Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities; Vol 3 No 3 (2018): KIU Journal of Humanities, Vol. 3 No. 3, September 2018, 2018)
This issue of KIU Journal of Humanities touches on Human Rights, Religious Studies, Language and Literary Studies, Development Administration, Educational Psychology and Educational Technology. The first part of the Journal focuses attention on Human Rights. It is universally accepted that education is considered as a precondition for a healthy democratic society. Therefore it is thus important that Human rights education should include peace, democracy, development and social justice, as set forth in international and regional human rights instruments, in order to achieve common understanding and awareness with a view to strengthening universal commitment to human rights. It is against this backdrop that one of the papers in this part evaluates the implementation of UNESCO Rights Based Early Childhood Education programme in selected Anglophones West African Countries. Religious Education is an essential component of a broad and balanced education. It enables people to consider and respond to a range of important questions related to their own spiritual development, the development of values and attitudes and fundamental questions concerning the meaning and purpose of life. This is why all the papers in part three address different religious issues such as pastoral authority, sacrifices, sexuality and peaceful co-existence. Articles in the third part of this edition center on Language and Literary Studies. It is impossible for any nation of the world to attain any form of development when its people are not properly developed. This is because nations are built or developed through knowledge; and all forms of knowledge are transmitted through language. In other words, language mediates mental access to phenomena and, therefore, what we perceive is phenomena in the form in which language mediated our perception. The fact of the mediations of mental access to phenomena by language makes knowledge communicable. While language mediates between object and perception, literature is an embodiment of object, language and perception. The works of some African writers were x-rayed in this section to show the uniqueness of African Literature It has been discovered that Educational Psychology studies various factors which have impacts upon students, which may include family background, social groupings, peer groups, his / her emotional sentiments, and mental hygiene etc.  One of the papers in the section that focuses on educational psychology revealed that Secondary school teachers with more years of teaching experience produce students with high academic performance than their counterpart who have less experience in teaching. Based on the findings of this study, it is recommended that qualified and experienced teachers should be employed in the teaching profession and they should be provided with more incentives and better promotional prospects. Educational Technology has absolutely revolutionized the entire education system. Until recently, the teachers used to be the sole interpreter of knowledge to the learners and the textbooks the sole resource. Educational technology has affected the conventional roles and it has opened up the new areas of teacher functions such as management of resources and management of learning. Today, teachers have a range of media to assist and supplement the instructional work. Teachers can even specify the learning intentions, select the topic, identify the stimulus situation, determine media, manage teaching and finally conduct evaluation and modify the instructions in the light of evaluation results. Educational process cannot proceed systematically without the help of educational technology. Every aspect of educational system is fully enlightened with educational technology. This is why a few papers in this issue highlight ideas on how students can acquire teaching and learning skills through the use of modern technologies. Based on the their findings, the papers in this section recommend among others that science and technology education should be given greater emphasis in real life situation in the Nigerian socio-economic milieu. Above all, this edition of KIU Journal of Humanities features educative and informative articles. We hope that these thought provoking articles will contribute immensely to the existing knowledge on each topic.